The Palgrave Handbook of African Women's Studies
54 illus., 37 illus. in color. eReference.
Keywords: This definitive handbook is the first reference of its kind bringing together knowledge, scholarship, and debates on themes and issues concerning African women everywhere. It unearths, critiques, reviews, analyses, theorizes, synthesizes and evaluates African women’s historical, social, political, economic, local and global lives and experiences with a view to decolonizing the corpus. This Handbook questions the gendered roles and positions of African women and the structures, institutions, and processes of policy, politics, and knowledge production that continually construct, deconstruct, and reconstruct African women and the study of them. Contributors offer a consistent emphasis on debunking erroneous and misleading myths about African women's roles and positions, bringing their previously marginalized stories to relief, and ultimately re-writing their histories. Thus, this Handbook enlarges the scope of the field, challenges its orthodoxies, and engenders new subjects, theories,and approaches. This reference work includes, to the greatest extent possible, the voices of African women themselves as writers of their own stories. The detailed, rigorous and up-to-date analyses in the work represent a variety of theoretical, methodological, and transdisciplinary approaches. This reference work will prove vital in charting new directions for the study of African women, and will reverberate in future studies, generating new debates and engendering further interest.